The application of green solvents in separation processes - Pena-Pereira, Francisco; Tobiszewski, Marek (Elsevier, 2017)
The Application of Green Solvents in Separation Processes features a logical progression of a wide range of topics and methods, beginning with an overview of green solvents, covering everything from water and organic solvents, to ionic liquids, switchable solvents, eutectic mixtures, supercritical fluids, gas-expanded solvents, and more. In addition, the book outlines green extraction techniques, such as green membrane extraction, ultrasound-assisted extraction, and surfactant-mediated extraction techniques. Green sampling and sample preparation techniques are then explored, followed by green analytical separations, including green gas and liquid capillary chromatography, counter current chromatography, supercritical fluid chromatography, capillary electrophoresis, and other electrical separations. Applications of green chemistry techniques that are relevant for a broad range of scientific and technological areas are covered, including the benefits and challenges associated with their application.--Provided by publisher.